A Requirement Model for Customer Complaint System Based on CRM: A Case of Universiti Utara Malaysia - Rimansyah, Muhammad Nanda (2012)
Customer complaints’ play an important role in improving the services in higher institutions, and it is important to know how to handle them more efficiently in order to keep and maintain the relationships with the “customers” such as student, alumnae, staff members, faculty (college) members, and etc. At the moment, the customer can only lodge their complaints, but their problem might not be entertained. This project is focused on deriving a requirement model of the customer complaint system for universities based on CRM perspective. A prototype is developed based on the proposed requirement model and this prototype is evaluated by using perceived usefulness and ease of use where the respondents are from Universiti Utara Malaysia (UUM) students. The feedbacks from 50 respondents about the system prototype are quite good which are showed with 5.46 grand mean for perceived usefulness factor and 5.37 grand mean for perceived ease of use factor with the scale of 7. Therefore, it can be concluded that the prototype is useful and easy to use. This requirement model is expected to facilitate the other university to develop and enhance the system for customer complaint.